Organizational metaphors present in Venezuelan Higher Education Institutions (Praxis Educativa, 2022)
The present work aimed to phenomenologically categorize the organizational metaphors present in Venezuelan Higher Education Institutions. It was based on the qualitative paradigm with a phenomenological socio-historical approach, using the steps of the phenomenological method: previous, descriptive, structural and discussion of the results. In-depth, unstructured interviews were conducted with two academic vice-rectors of the Universidad del Zulia and Universidad Rafael Belloso Chacín. As a result, the presence of organizational metaphors was evidenced in the key informants' speeches: Living organism, Evolution, Politics, Crisis, Cybernetic machine, Knowledge as power, Change, Participation, Discord and Technology as power. Finally, it was shown that the use of organizational metaphors provides a different alternative for the study of universities, thus allowing to open new schemes for their understanding and comprehension in highly complex environments.
Keywords: organizational metaphor; institutions of higher education; organization; university, phenomenological approach.